Spinal Cord Infarction in a Patient with Hereditary Spherocytosis: A Case Report and Discussion - Waqar Waheed; Anjali L. Varigonda; Chris E. Holmes; Christopher Trevino; Neil M. Borden; W. Pendlebury (Case Reports in Neurological Medicine)
The etiology of spinal cord infarcts (SCIs), besides being related to aortic perioperative events, in large subset of SCIs, remains cryptogenic. We present a first case of SCI in a patient with hereditary spherocytosis and discuss the potential pathophysiologic considerations for vascular compromise. A 43-year-old woman with a history of hereditary spherocytosis, post splenectomy status, presented with chest, back, and shoulder pain with subsequent myelopathic picture; SCI extending from C4-T2 was confirmed by MRI. Despite aggressive treatment her stroke progressed leading to her demise. Her autopsy confirmed the SCI and revealed some incidental findings, but the cause of SCI remained unidentified. Exclusion of the known etiologies of SCI by extensive negative workup including autopsy evaluation suggested that SCI in our case was related to her history of hereditary spherocytosis. Both venous and arterial adverse vascular events, at a higher rate, have been associated in patients with hereditary spherocytosis who had their spleens removed compared to nonsplenectomized patients. Postsplenectomy increases in the platelet, red blood cell count, leukocyte count, and cholesterol concentrations are postulated to contribute to increased thrombotic risk. Additional prothrombotic factors include continuous platelet activation and adhesion as well as abnormalities of the red blood cell membrane.